Analisis Pengelolaan Risiko Perusahaan Dalam Menghadapi Krisis Ekonomi Global: Pada Perusahaan CV Berkawan Distribution di Kabupaten Bangkalan - Fauzan, Ach; Djasuli, Mohamad (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
In this discussion, mangulas means risk management analysis in conditions of the global economic crisis. Want to explain why the global economic crisis is intertwined, the factors that can affect the industry, and how the industry can prepare and respond to the crisis. CV Berkawan Distribution's industry in Bangkalan Regency is experiencing serious challenges in protecting its operational stability and business development. As an industry that moves in the distribution of objects, CV Berkawan Distribution is closely related to the general economic situation that affects the relationship between reserves and market demand. This research intends to analyze how CV Berkawan Distribution manages the risks arising from the impact of the general economic emergency. The analysis will relate the identification of risks that are very likely to be intertwined, the risk management strategies that have been applied by the industry, and the assessment of the usefulness of those strategies in experiencing broad economic challenges. In this study, researchers used a qualitative approach with the type of case study research (case study) and was descriptive. In this study, data collection techniques in depth on CV Berkawan Distribution in Bangkalan Regency. This will link the collection of information from various sources, including interviews with industrial management, analysis of documents in the industry, and direct monitoring of the conclusion in this study is In experiencing economic challenges, a good strategy must mix these elements to achieve maximum results. Not only that, it means to know that there is no one-dimensional strategy suitable for all. Each economic entity must familiarize its strategy with its specific conditions and desires, With Strategies, together with regular adaptation and assessment, can help CV Berkawan Distribution to mitigate the effects of economic emergencies and increase its resilience to the risks associated.